Reconstructing Global Narratives: The Contribution of Cross-Cultural Perspectives to Understanding History and World Literature - Mursyid, Istianah; Vidya, Siska Mei; Maghfiroh, Faza Lailatul; Nisa, Auliyah Khoirun (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Amid global uncertainties marked by pandemics, international conflicts, climate crises, and mass migration, it is crucial to reconsider how we understand history, language, and literature through a cross-cultural perspective. Global historical narratives have often centered on dominant viewpoints, frequently overlooking the contributions and experiences of non-Western cultures. Similarly, the use of language and the development of literature have often reinforced certain cultural hierarchies, thus limiting the diversity of human experience representation. This paper highlights the importance of expanding cross-cultural approaches to reconstruct a fairer historical narrative, to value linguistic diversity, and to position global literature as a medium for intercultural dialogue. Through an interdisciplinary qualitative approach, drawing on the ideas of figures such as Edward Said, Gayatri Spivak, Ngũgĩ wa Thiong’o, and Dipesh Chakrabarty, this study proposes the need to create space for alternative histories, minority languages, and world literature. Strengthening cross-cultural perspectives, therefore, becomes a vital step in building cultural resilience, deepening global empathy, and fostering international solidarity in the face of contemporary challenges.